Conventional and microwave drying of kefir grains: effect on drying, rehydration and fermentation kinetics and viability of kefir grains - Karabekiroglu, Sena Nur; Kilic, Dilek (WALTER DE GRUYTER GMBH, 2025)
In the present work, impacts of microwave and oven drying on the drying, rehydration, and fermentation kinetics of kefir grains as well as on the microbial viability of grains were investigated. Kefir grains were dried at various oven temperatures (30 degrees C, 37 degrees C, and 45 degrees C) and microwave powers (100 W, 180 W, and 300 W). Microwave drying reduced the drying time by 90 % and water absorption capacity of grains dried by microwave is higher than those dried by the oven. Moisture diffusivity was observed to increase with drying temperature (0.4 x 10-10-1.7 x 10-10 m2/s) and microwave power (3.2 x 10-10-17 x 10-10 m2/s). The results indicated that drying methods and conditions do not affect the fermentation ability and the viability of kefir grains to a detrimental extent. Compared to spray and freeze drying, the survival rate in microwave and oven drying (around 90 % for both LAB and yeast) was significantly high. As a result of the modeling studies, it was determined that the drying kinetics could be represented by the 1st order kinetic model (Lewis model) while the rehydration and fermentation kinetics could be represented by the pseudo 1st order kinetic model.
Keywords: kefir; drying; microwave; rehydration; fermentation; kinetics; HEALTH; Food Science & Technology